THE IMPACT OF WORKLOAD OVERLOAD IN NURSING AND ITS CONSEQUENCES FOR PATIENT CARE - Samartino, Camila Alves; Miranda, Maria Antonia Queiroz; Nunes, Clarissa Albuquerque Vaz; da Silva, Livia Moreira; Eleutério, Bruna Marçal Guidoti; da Silva, Fabricio Sidnei; Spaziani, Amanda Oliva; Franco, Rauer Ferreira (Seven Editora, 2026)
This integrative review analyzes the impact of nursing workload and burnout on patient safety and the quality of care. The global shortage of professionals, combined with stressful environments, generates high exhaustion rates, which were dramatically exacerbated by the COVID-19 pandemic. The study consistently demonstrates that inadequate nurse-to-patient ratios are directly associated with increased hospital mortality, higher readmission rates, and prolonged lengths of stay. Additionally, team burnout correlates with a lower safety climate and an increase in adverse events, encompassing healthcare-associated infections, medication administration errors, and the omission of essential vigilance and hygiene care. Contrary to the perception of high cost, economic analyses show that investing in adequate staff sizing yields a positive return, as costs are offset by the reduction in complications. It is concluded that workload must be addressed as a systemic organizational phenomenon. Adopting safe minimum ratio policies is cost-effective, essential for mitigating risks, and fundamental for preserving lives.